Challenge for learners of Lithuanian as a second language: variation of pronouns - Ramonaitė, Jogilė Teresa (Lietuvių kalba, 2019)
The paper analyzes Lithuanian personal pronouns that are a challenge for learners of Lithuanian as a second language. The pronouns studied refer to ‘he’ and ‘she’ and correspond to jis and ji in the standard Lithuanian language as described in the Grammar of Modern Lithuanian and Dictionary of Modern Lithuanian and Lithuanian L2 textbooks. However, the repertoire of the spoken Lithuanian as demonstrated by the data of spoken corpora, consists of four pronouns: jis/jisai for masculine and ji/jinai for feminine. The analyses of the Lithuanian as a second language learners’ corpus shows that this variation of the natives’ speech is not really acquired by the second language learners and it does present a challenge in the more advanced stages of acquisition. If the beginning learners do not seem to notice this variation at all, some advanced speakers do incorporate the longer spoken variants into their speech but to extreme proportions and therefore overuse them when comparing to the native speakers. Also, at least one case shows the longer variants being not transparent enough to be acquired from the environment. This poses a variety of questions, also related to the necessity of studying the spoken variety of Lithuanian by the native speakers.
Keywords: Lithuanian as a second language; variants or pronouns; pronoun he; pronoun she